A systematic review of the impact of long-term endurance training on negative cardiac remodelling in athletes: can we do too much exercise? - Gosden, J. A. G. (Research Square, 2024)
Background The benefits of undertaking regular physical exercise in lowering the risk of cardiovascular disease is recognised. However, there is concern surrounding the negative cardiac remodelling that can ensue from excessive training. The systematic review aimed to examine the point at which endurance trainingbecomes detrimental to the left ventricle and whether risk reduction guidelines should be introduced.